TEM STUDY OF SHOCK METAMORPHISM IN QUARTZ FROM THE SEDAN NUCLEAR TEST SITE - Cordier P.; Gratz A.J. (My University, 1995)
Nuclear explosions represent a useful simulation of meteorite impacts. Stresses of tens of gigapascals are produced during detonation and stress pulses can last 0.1 ms or longer, which is 3-4 orders of magnitude longer than laboratory experiments. Samples studied here were taken from the ejecta of the Sedan nuclear test site and consist of a coarse-grained granodiorite containing quartz, plagioclase, K-feldspar, cordierite and hornblende. Shocked quartz grains were selected optically in thin section and studied by TEM. TEM reveals the presence of planar deformation features (PDFs), which consist of multiple sets of planar amorphous lamellae with the crystallographic orientations {1013}, {1012}, and rarely {1011}. Some lamellae exhibit a substructure which consist of amorphous sublamellae organized 'en echelon'. No high-pressure phases were detected along the transformation lamellae. Some lamellae show evidence of beginning recrystallization, which probably occurred during cooling of the hot ejecta. The shock-induced defects present at the Sedan site are very similar to those seen in laboratory shock recovery experiments and also to those present at meteorite impact craters (e.g., Meteor Crater or Ries Crater). This suggests that shock-induced amorphization in quartz is not strongly dependant on shock pulse duration.